INFERIORITY FEELINGS FROM COMPETITIVE UPWARDS: ADOLESCENT'S DIGITAL CULTURE AND SCHOOL COUNSELOR'S ROLE - Rahmania, Desriani; Adiwinata, Anne Hafina; Sugandhi, Nani M (CV. TOTUS TUUS, 2023)
Striving for Superiority is one of the personality dimensions from Alfred Adler's theory. Striving for superiority can help adolescents balance their sense of inferiority, so that adolescents have better understanding of their identity roles. Adolescents have a high curiosity tendency to their self-development although at the same time faced inferiority feelings. Adolescent faced the rush of development of technology and the social media era, where the idea of the ideal are everywhere in digital culture. Because of that the majority of adolescents have biased and polarized perspectives in their exploration, so that adolescents need a growth mindset. The school counselor's role guides adolescents to be optimal in adolescent development, by developing a growth mindset, adolescents willing to do self-exploration and understand their identity. The purpose of this study is to know the role of the school counselor on developing adolescents' growth mindset to adjust in inferiority feelings while striving for superiority. The method uses a systematic literature review conducted by 12 recommendations and using criteria for adolescents. The school counselor as a psychoeducational service performs many actions therefore, school counselors are needed developing adults a growth mindset to face inferiority, it focus on cognitive stimulation. The result has a recommendation focus on conceptual of growth mindset on cognitive behavioral intervention such as reframing, journaling, and bibliotherapy.